Bridging the socioeconomic divide: Unveiling the impact of energy transition on communities - Istiqomah, Meilia (Institute for Advanced Social, Science, and Sustainable Future, 2025)
Background: This study focuses on Indonesia’s energy transition, a shift from non-renewable to renewable energy sources aimed at reducing environmental impacts and promoting socioeconomic benefits. The transition’s effect on energy consumption, employment, and public support is analyzed, with particular attention to challenges in remote areas. Method: This study uses a qualitative approach with Systematic Literature Review (SLR) to analyze the energy transition in Indonesia based on 24 journals and government regulations. The analysis was conducted using the Driving Forces – Pressures – State – Impacts – Responses (DPSIR) framework, which links social, economic, and environmental factors to provide impacts and responses to the energy transition. Findings: The energy transition has significant socioeconomic impacts, such as increased public awareness of renewable energy's importance. Notable changes include rising energy consumption in industrial and construction sectors, job creation with around 400,000 new opportunities in renewable energy, and growing interest in electric vehicles and rooftop solar panels. However, challenges related to cost, infrastructure, and technology reliability remain. Public support for energy transition initiatives exceeds 80%. Conclusion: Achieving a successful energy transition requires collaborative efforts from all stakeholders, addressing both the opportunities and challenges to ensure sustainable energy resources and positive socioeconomic outcomes. Novelty/Originality of this article: This study provides a comprehensive analysis of the effects of energy transition on socioeconomic conditions, highlighting the increasing public support for renewable energy and its impact on job creation, energy consumption, and behavioral changes, which have not been extensively explored in existing literature.